Partial Replacement of Synthetic Vitamin E by Polyphenols in Post-Weaning Piglets - Grazia Pastorelli; Rachida Benamri; Massimo Faustini; Roberta De Bellis; Valentina Serra; Lauretta Turin; Marc Haumont; Philippe Durand; Laura Bianchessi; Emmanuelle Prost-Camus; Thomas Pecqueur; Michel Prost (MDPI AG, 2023)
Vitamin E is an essential nutrient usually recommended in post-weaning piglets, when a decline in the serum vitamin E concentration is observed. Selected polyphenols have the potential to partially replace vitamin E in animal feed. The aim of this study was to investigate the effect of the dietary inclusion of some commercial polyphenol products (PPs) on the growth performance, antioxidant status and immunity of post-weaning piglets. A total of 300 piglets (BW 7.18 kg ± 1.18) were randomly assigned to six dietary groups: CON− (40 mg/kg vitamin E); CON+(175.8 mg/kg vitamin E); and PP1, PP2, PP3 and PP4, in which 50% vitamin E of CON+ was replaced with PP with equivalent vitamin E activity. The PP1 group exhibited lower performance (p < 0.05) than the other dietary groups, but a similar performance to that commonly registered in pig farms. Dietary polyphenols did not influence the IgG concentration or the IL-6, IL-10, IFN-γ and TNF-α cytokine concentrations. A lower IL-8 level was found in the PP4 group than in the other groups. The diets that affected the vitamin A content showed the highest value (p < 0.05) in the PP1 group, and a trend was noted for vitamin E with a higher content in PP4 and CON+. The polyphenols-enriched diets, especially the PP3 diet, maintained an antioxidant capacity (whole blood KRL) similar to the CON+ diet. In conclusion, the replacement of vitamin E with all PPs enables partial vitamin E substitution in post-weaning piglets.